Government Policy to Encourage Customers to Support Development of Renewable Energy in Indonesia – A Proposal. - Atmonobudi Soebagio; Bambang Widodo (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2017)
Indonesia is blessed with abundant renewable energy resources. Nevertheless, they have only been used to cover about 5% of the total national energy demand. To optimize their utilization, the government has to make and implement a policy that will encourage PLN costumers to help increase their on-grid power supply capacity. This policy will provide benefits for islands that are already equipped with PLN power grids. This paper uses Solar Power Plants and household costumers as models to calculate potential on-grid power increase which can be contributed by PLN costumers. A two-way power meter is used to replace the currently used one. This model will be applied to the conventional grid to demonstrate the compatibility that show how it is applicable even without upgrading the conventional grid to become smart grid system. The result shows that customers can participate significantly through the flow of their excess energy to grid.